Komitmen Organisasi Perawat di Rumah Sakit Dr. Reksodiwiryo Padang - Firda Damba Wahyuni; Rizanda Machmud; Jafril (LLDIKTI Wilayah X, 2019)
Nurses who stay at the hospital show employees who have organizational commitment. Low organizational commitment can increase workplace accidents, wound infections, increase mortality and turnover rates. This study aims to obtain an overview of the factors associated with organizational commitment at Dr. Reksodiwiryo Padang. This type of quantitative research with cross sectional design. The number of respondents was 142 nurses. The sampling technique in this study is proportionate stratified random sampling. Data analysis uses Chi-Square test. The results found there is a relationship between workload factors with organizational commitment of nurses (p = 0.006, α = 0.05), there is a relationship between work stress factors and nurse organizational commitment (p = 0.003, α = 0.05), there is a significant relationship between job satisfaction factors with organizational commitment of nurses (p = 0.002, α = 0.05). The conclusion of this research is that there is a relationship between workload, work stress and job satisfaction with organizational commitment. It is recommended to the Hospital Director to make policies for optimizing the welfare of nurses based on career paths that are included in the calculation of remuneration with achieving 100% remuneration Perawat yang bertahan pada rumah sakit menunjukkan karyawan yang mempunyai komitmen organisasi. Rendahnya komitmen organisasi dapat meningkatkan kejadian kecelakaan di tempat kerja, infeksi luka, peningkatan mortalitas dan turnover rate. Penelitian ini bertujuan untuk memperoleh gambaran faktor-faktor yang berhubungan dengan komitmen organisasi di RS Dr. Reksodiwiryo Padang. Jenis penelitian kuantitatif dengan desain cross sectional. Jumlah responden adalah 142 perawat. Teknik pengambilan sampling dalam penelitian ini adalah proportionate stratified random sampling. Analisa data menggunakan uji Chi – Square. Hasil penelitian didapatkan ada hubungan faktor beban kerja dengan komitmen organisasi perawat (p=0.006, α=0.05), ada hubungan faktor stress kerja dengan komitmen organisasi perawat (p=0.003, α=0.05), ada hubungan yang bermakna antara faktor kepuasan kerja dengan komitmen organisasi perawat (p=0.002, α=0.05). Kesimpulan penelitian diketahui ada hubungan faktor beban kerja, stres kerja dan kepuasan kerja dengan komitmen organisasi. Disarankan kepada Direktur Rumah Sakit membuat kebijakan pengoptimalan kesejahteraan perawat berbasis jenjang karir yang dimasukkan pada perhitungan remunerasi dengan pencapaian remunerasi 100%.